Effectiveness of a cognitive behavioral therapy program in stroke patients in the Republic of Korea: a mixed-methods study - So-Eun Choi; Deok-Ju Kim (Osong Public Health and Research Perspectives)
Objectives This study aimed to explore the effects of a cognitive behavioral therapy (CBT) program on stroke patients, as well as their experiences participating in the program. Methods This study employed a mixed-methods design, integrating qualitative case studies with quantitative analysis. We included 20 stroke patients, randomly divided into 2 groups of 10 each: an experimental group and a control group. The experimental group underwent a CBT program comprising 20 sessions, in addition to receiving general occupational therapy. Conversely, the control group participated in meditation relaxation sessions alongside their general occupational therapy. Both interventions were administered daily for 60 minutes, 5 days a week, over a 4-week period. Results After the intervention, the experimental group exhibited significant improvements in depression, anxiety, self-efficacy, and rehabilitation motivation (p<0.01, p<0.05). In contrast, the control group only demonstrated a significant reduction in anxiety (p<0.05). A comparison of the changes between the 2 groups showed significant differences in depression and anxiety (p<0.01), but no significant differences in self-efficacy and rehabilitation motivation (p>0.05). In-depth interviews with 10 participants from the experimental group were conducted and analyzed, revealing 4 core themes: “psychological stability,” “physical symptom relief,” “altered daily routines,” and “challenges and hopes for change.” Conclusion The findings of this study suggest that CBT programs may serve as a valuable intervention, offering psychological support and rehabilitation for stroke patients.